Corporate Governance, Pengaruhnya Terhadap Kualitas Informasi Investor Atas Bumn Terprivatisasi - Dwi Lusi Tyasing Swastika (Conference In Business, Accounting, And Management (CBAM), 2012)
Most of the SOEs in developing countries, especially Indonesia has a weakness governance, among other issues that cause agency problems of government intervention in the management of SOEs is high. Corporate governance is expected to serve to suppress or reduce the agency cost due asymetric information, that the more managers (agent) know internal information and the company’s prospects in the future compared with shareholders and stakeholders (principal). This research was conducted to determine the extent to which corporate governance is measured by Shareholders’ Meeting Index, Board of Director Index, Firm’s Transparency Index, affect the quality of investor information as indicated by the value of the bid-ask spread on investments in privatized SOEs. The research sample was privatized 11 SOEs for the period 2008-2011, totally 44 observations. By using multiple linear regression analysis, the results showed that Shareholders’ Meeting Indexof corporate governance significantly influences the quality of investor information.Keywords: asymetric information, corporate governance, the quality of investor information, privatized SOEs.